Stages of Cognitive Development and Curriculum Construction (Critical Analysis of Piaget's Theory of Cognitive Development) - M. Faqih; Lukmanul Hakim; Muhammad Iqbal (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This research plan departs from interviews with parents and several educational practitioners regarding problems in implementing the 2013 Curriculum. The results of these interviews show that the competency demands that elementary school students must master today are more complex than in the previous curriculum implementation period. The subject matter taught to elementary school students, especially in the upper grades (grades 4 to grade 6), is material that was previously taught at the junior high school level, perhaps even in some high schools. Referring to Piaget's theory of cognitive development, the construction of the 2013 curriculum is designed in such a way as to engineer children's cognitive development beyond their biological age. If according to Piaget, the last stage of cognitive development is formal operational which is reached after children are 11 years old or more, then in the construction of the 2013 Curriculum it is necessary to assume that children are encouraged to reach this cognitive stage more quickly. This research aims to test whether the stages of cognitive development according to Piaget are still relevant to the current condition of students in Indonesia. The duration of the research is 6 months with a quantitative approach. The unit of analysis is elementary school students in Mataram City whose level of cognitive development will be measured. Research outputs are targeted in research results reports and articles published in accredited national journals Sinta 3 or international journals. The TKT that is expected to be achieved is at level 3, namely confirmation of the relevance of a theory and basis for determining policy, especially in developing educational curricula.